BIM can help decarbonize the construction sector: Primary life cycle evidence from pavement management systems. (10th March 2023) - de Bortoli, Anne; Baouch, Yacine; Masdan, Mustapha
Abstract: Transforming the construction sector is key to reaching net-zero, and many stakeholders expect its decarbonization through digitalization, but no quantified evidence has been brought to date. This article proposes the first environmental quantification of the impact of Building Information Modeling (BIM) in the construction sector. Specifically, the direct and indirect greenhouse gas (GHG) emissions generated by a monofunctional BIM to plan road maintenance – a Pavement Management System (PMS) - are evaluated using field data from France. The related carbon footprints are calculated following a life cycle approach, using different sources of data – including ecoinvent v3.6 – and the IPCC 2013 GWP 100a characterization factors. Three design-build-maintain pavement alternatives are compared: scenario 1 relates to a massive design and surface maintenance, scenario 2 to a progressive design and pre-planned structural maintenance, and scenario 3 to a progressive design and tailored structural maintenance supported by the PMS. First, results show the negligible direct emissions due to the PMS existence – 0.02% of the life cycle emissions of scenario 3's pavement, e.g. 0.52 t CO2eq for 10 km and 30 years. Second, the base case and two complementary sensitivity analyses show that the use of a PMS is climate-positive over the life cycle when pavement subgrade bearing capacity improves over time, neutral for the climate otherwise. The GHG emissions savings using BIM can reach up to 14 and 30% of the life cycle emissions respectively compared to scenario 2 and 1, and resp. 47 and 65% when restraining the scope to maintenance and rehabilitation and excluding original pavement construction. Third, the neutral effect of BIM in case of a deterioration of the bearing capacity of the subgrade may be explained by design practices and safety margins, that could in fact be enhanced using BIM. Fourth, the decarbonization potential of a multifunctional BIM is discussed, and research perspectives are presented. Highlights: The GHG emission balance from using BIM in construction is quantified for the first time. BIM usage to tailor pavement maintenance is globally positive for the climate. Life-cycle GHG reduction can reach up to 30%, and up to 65% for maintenance stage. Direct emissions from the manufacturing and operation of BIM are negligible (0.02%). GHG consequences from other BIM usages than tailored maintenance must be checked.